PENGARUH IKLIM KERJA,KOMPETENSI DAN KARAKTERISTIK INDIVIDU TERHADAP KINERJA PEGAWAI NEGERI SIPIL PADA UPTD PELAYANAN PAJAK DAN RETRIBUSI DAERAH PROVINSI BALI DI KOTA DENPASAR - Ni Kadek Mita Ayulia Pramesti; Nengah Landra; Ida Bagus Widiadnya (EMAS, 2021)
Employee performance in general is a manifestation of work performed by employees which is usually used as a basis or reference for evaluating employees within an organization. This study aims to test and obtain empirical evidence of the influence of the work climate, competence and individual characteristics on employee performance at the UPTD Regional Tax and Retribution Services of Bali Province in Denpasar City. The population in this study were 79 employees. The sample in this study was 79 people, namely the entire population representing the sample. This research was conducted at the UPTD of Bali Provincial Tax and Retribution Services in Denpasar City. The results showed that the work climate, competence and individual characteristics had a positive and significant effect on employee performance. Data collection was carried out through questionnaires. The analysis technique used is instrument test, classical assumption test, multiple linear analysis, multiple correlation analysis, determination analysis and hypothesis testing (t test). The results showed that the work climate, competence and individual characteristics had a positive and significant effect on employee performance at the UPTD Regional Tax and Retribution Services for the Province of Bali in Denpasar City. Future research can develop this by using other variables which theoretically have an influence on performance.